2022
DOI: 10.1039/d2sc00274d
|View full text |Cite
|
Sign up to set email alerts
|

DNP NMR spectroscopy enabled direct characterization of polystyrene-supported catalyst species for synthesis of glycidyl esters by transesterification

Abstract: Polymer-supported catalysts have been of great interest in organic syntheses, but have suffered from the difficulty to obtain direct structural information regarding the catalyt species embedded in the polymer due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Nitrogen centers of many organic and inorganic molecules are active or potentially active for various non-covalent and coordinative interactions. , The low natural abundance and the gyromagnetic ratio of the 15 N isotope make its detection difficult. However, this problem can be solved either by isotopic labeling , or by specially designed NMR methods. In this work, the experimentally measured 15 N NMR chemical shift tensors (CSTs) will be compared with the calculated nitrogen absolute shielding tensors in order to identify the molecules for which these tensors are close up to a constant. This constant is σ ref ( 15 N).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen centers of many organic and inorganic molecules are active or potentially active for various non-covalent and coordinative interactions. , The low natural abundance and the gyromagnetic ratio of the 15 N isotope make its detection difficult. However, this problem can be solved either by isotopic labeling , or by specially designed NMR methods. In this work, the experimentally measured 15 N NMR chemical shift tensors (CSTs) will be compared with the calculated nitrogen absolute shielding tensors in order to identify the molecules for which these tensors are close up to a constant. This constant is σ ref ( 15 N).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, investigators should try and adapt the various available protocols to their specific case, and this may prove daunting. This is especially true for polymer materials where careful optimization of sample preparation conditions is typically required to achieve meaningful results, [29][30][31][32][33][34][35][36] with no guarantee of success in the end. In parallel, supercritical CO 2 (scCO 2 ) impregnation has been used for a long time in the field of polymer materials to impregnate specific components (e.g., additives, active pharmaceutical ingredients, dyes, and organic metallic complexes) in a polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recent excellent work by Tanaka et al, revealed that glycidyl esters could be synthesized from glycidol and methyl esters via transesterification. 22,23 Other recent work by Ishihara et al, also disclosed the synthesis of glycidyl (meth)acrylate from a transesterification of methyl (meth)acrylate with glycidol. 24 However, there is no report on the alcoholysis of cyclic esters such as lactide and lactones by glycidol in the literature although copolymerization of glycidol and lactide were reported.…”
Section: Supajittra Yimthachote and Khamphee Phomphrai *mentioning
confidence: 99%